Examination of the psychometric properties of Arabic version of the Body Vigilance Scale - Abdallah Chahine; Ali Hemade; Christian-Joseph El Zouki; Sahar Obeid; Jean-Claude Lahoud; Feten Fekih-Romdhane; Souheil Hallit (PLoS ONE, 2025)
Introduction The Body Vigilance Scale (BVS) was designed and validated as a short and concise measure to assess attentional focus on bodily sensations and related processes. The BVS is available in the English language, but no Arabic version have been developed, and no validation of the scale exists in Lebanon. The current study aimed to determine the reliability, validity and factor structure of the Arabic version of the Body Vigilance Scale. Methods This study has a cross-sectional design. It was conducted from October 2 to November 20, 2024, enrolling Lebanese adults. The study was carried out in the Arabic language and included the BVS, the Patient Health Questionnaire, the Insomnia Severity Index and the Freiburg Mindfulness Inventory. Results In total, 641 participants participated in this study, with a mean age of 35.11 ± 12.67 years and 70.5% females. Internal reliability of BVS was adequate (ω = .87/ α = .86). Invariance was shown at the metric and scalar levels in terms of genders. A significantly higher mean BVS score was found in females compared to males. Higher depression (r = 0.26; p < 0.001), anxiety (r = 0.29; p < 0.001), insomnia (r = 0.29; p < 0.001) and mindfulness (r = 0.27; p < 0.001) correlated significantly with higher body vigilance scores. Conclusion The Arabic version of the BVS is a reliable and valid tool for assessing somatic attention in Arabic-speaking populations. Its psychometric robustness, demonstrated measurement invariance across genders, and associations with psychological distress measures underscore its utility in both clinical and research settings.